Rodinný dům - Hyxa, Petr (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Jedná se o dvoupodlažní částečně podsklepený rodinný dům se zakomponovanou garáží. Nosný systém je tvořen tvarovkami Medmax vyplněnými železobetonem. Stropní konstrukce je realizována ze stropních panelů Med10 a železobetonové nosné vrstvy. Objekt je založen na průběžných betonových pásech. Konstrukce krovu je vaznicového a krokevního typu tvořící sedlové střechy.

This is a two-floor detached house with partly basement and garage which is incorporated. The supporting structure is made up of bricks Medmax filled reinforced concrete. Construction of ceiling is realized from the panels Med10 and reinforced concrete, which is made carrying construction. The building is based on concrete foundations. Construction of the truss is purlin’s and rafter’s type. The roofs are forming a gabled shape.
Residential House
Keywords: Projektová dokumentace; rodinný dům; ztracené bednění - Medmax a Med10; Neopor; železobeton; betonové základy; vaznicová soustava; sedlová střecha.; Project documentation; residential house; sacrificial formwork - Medmax and Med10; Neopor; reinforced concrete; concrete foundations; purlin system; gabled roof.